Rural Bangladeshi consumers’ (un)willingness to pay for low-milled rice: Implications for zinc biofortification - Herrington, Caitlin L.; Maredia, Mywish K.; Ortega, David L.; Taleon, Victor; Birol, Ekin; Sarkar, Md Abdur Rouf; Rahaman, Md Shajedur (Wiley, 2023)
Zinc deficiency is a severe public health problem in Bangladesh. We examine the effects of nutritional information on rural consumers’ willingness-to-pay (WTP) for two ways to increase zinc intake through rice, the main staple crop–low-milling that gives rice grains a distinctive light brown color (a visible trait) and sets it apart from the culturally preferred high-milled white rice grain and biofortification of rice with increased zinc content (an invisible trait), which is also low-milled to retain maximum zinc content. Results of our economic experiments suggest that with nutritional information, consumers are willing to pay a premium of 4.6% for zinc biofortified rice compared to non-biofortified rice, when milled at the same level. However, results confirm the strong preference for high-milled rice by Bangladeshi consumers who discounted low-milled rice by 8%–10% even after receiving information on the nutritional benefits of biofortified or low-milled rice. We find that consumers’ WTP for the two high-zinc-low-milled rice types (biofortified and non-biofortified) is positively correlated with being a female, more educated, belonging to households engaged in non-farm activities and with children under 5 years of age. Results point to the importance of nutritional awareness campaigns for increasing zinc biofortified and low-milled rice consumption and guiding the targeting strategy for such campaigns. Given the consumer preference for high-milled rice, this study also points to the need for exploring the rice fortification strategy to address the challenge of malnutrition.